Peran Nyi Lucia Siti Aminah Subanto sebagai Dalang PEREMPUAN Wayang Wahyu dalam Lakon “Siswa Kang Cidra” - Seruni Widawati; Seruni Widaningrum; R Mohammad Luthfi Badaralam (Pusat Riset dan Inovasi Nasional, 2025)
Female puppeteers often face various obstacles in their personal and professional development due to the limitations imposed by social constructs, which dictate that female puppeteers must resemble their male counterparts in terms of style, technique, and character. In this context, gender becomes a barrier that hinders women from fully expressing their identity and creativity freely within the world of wayang (traditional Javanese puppetry). As a result, few women dare to develop their personal perspectives and thoughts into artistic works. In fact, women possess great opportunities and significant potential to create and cultivate wayang literature in innovative and meaningful ways. Amidst these challenges and prevailing stereotypes, Nyi Lucia Siti Aminah Subanto remains consistently active in her creative pursuits, particularly in the development of wayang wahyu (a type of Christian-themed wayang). Her distinctive style and artistic approach greatly contribute to her presence in the world of puppetry and radio media. This study examines gender roles, the characteristics of her pakeliran (performance), and her contributions to the Wayang Wahyu community “Ngajab Rahayu,” using theories by Kamla Bhasin, Sunuh, Robbins, and Gibson.